2018
DOI: 10.3791/57254
|View full text |Cite
|
Sign up to set email alerts
|

Magnet Assisted Composite Manufacturing: A Flexible New Technique for Achieving High Consolidation Pressure in Vacuum Bag/Lay-Up Processes

Abstract: This work demonstrates a protocol to improve the quality of composite laminates fabricated by wet lay-up vacuum bag processes using the recently developed magnet assisted composite manufacturing (MACM) technique. In this technique, permanent magnets are utilized to apply a sufficiently high consolidation pressure during the curing stage. To enhance the intensity of the magnetic field, and thus, to increase the magnetic compaction pressure, the magnets are placed on a magnetic top plate. First, the entire proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The visual demonstration of the composite lay-up preparation using the WLVB process can be found in Ref. [33]. Briefly, the steps are as follows: the 38.1 × 25.4 cm 2 area of 400-series stainless steel tool plate was covered by a release film for easy removal of the laminate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The visual demonstration of the composite lay-up preparation using the WLVB process can be found in Ref. [33]. Briefly, the steps are as follows: the 38.1 × 25.4 cm 2 area of 400-series stainless steel tool plate was covered by a release film for easy removal of the laminate.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, a cost-effective, flexible method to apply sufficiently high consolidation pressure in WLVB processes can have certain benefits in the manufacture, repair, and maintenance of large composite parts. Towards this goal, Neodymium Iron Boron (NdFeB) permanent magnets have been recently used to generate up to 0.8 MPa compaction pressure on the vacuum bag lay-up [31,32,33,34]. It was shown that by the stationary placement of permanent magnets during cure of the glass/epoxy laminates, both the flexural strength and modulus increased in excess of 46% due to a 70% reduction in void content to less than 2% and a 55% increase in fiber volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, NdFeB magnets were used to apply consolidation pressure during wet lay-up/vacuum bag process and out-of-autoclave prepreg curing to improve laminate properties. [30][31][32] In the present study, two sets of magnets, magnetized through the thickness, were used for inducing different levels of pressure. The first set (A) includes N52-2.54 Â 2.54 Â 1.27 cm 3 NdFeB magnets with a surface magnetic field of 0.49 T. The second set (B) contains N52-2.54 Â 2.54 Â 5.08 cm 3 NdFeB magnets, which are thicker and can generate a stronger surface magnetic field of 0.71 T. The pull force generated by one magnet placed on a top steel plate is measured as a function of the gap from a bottom steel plate using a mechanical testing machine.…”
Section: Neodymium Permanent Magnetmentioning
confidence: 99%
“…Both offer numerous benefits such as multifunctional design, production, and structural flexibility and tailoring [11,12]. Biomedical devices [13,14], field-assisted fabrication [15][16][17], surgical [18,19], electronics and sensing [20][21][22][23][24][25], and soft robotics/actuators/stiffening [26][27][28][29][30][31][32][33] are amongst the most common applications for magnetic composite materials. Investigations have been conducted to provide a description of the mechanical properties affected by a magnetic field [34,35].…”
Section: Introductionmentioning
confidence: 99%